HUBUNGAN POWER OTOT LENGAN BAHU DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA SISWA PUTRA KELAS XI SMK TARUNA MANDIRI PEKANBARU - M.Qailani Maulana; Saripin '; Ni Putu Wijaya Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract ,: problem in this researck is less than the maximum power arm muscles shoulder and back muscle flexibility with shot put results. This is because by the factor of the physical condition of male students of class XI SMK Taruna Mandiri Pekanbaru is still lacking, especially on the power arm muscles shoulder and flexibility of back muscles are visible when male students do repulsion, results tolakannya less than the maximum can be seen from the deficiencies in the current do prefix, while holding the bullet, bullet exit position, the arm strength and position of the body at the time refused. The sample in this study was the son of a class XI student of SMK Taruna Pekanbaru. A sampling technique that the overall population (total sampling). The instrument used in this study is to test two hand medicine ball put and sit and reach test, which aims to measure the strength of the shoulder arm muscle power and flexibility of the back muscles and then test their skills are shot put test that aims to measure the far distance repulsion. After that, the data is processed with statistical, normality test with lilifors test at significant level 0,05α. The hypothesis is that the alleged relationship between Power are the shoulder and arm muscles muscle tone back to the shot put results on male students of class XI SMK Taruna Mandiri Pekanbaru. Based on analysis of test lilifors produce L0maks (X1) (0108) <Lt (0173), L0maks (X2) (0132) <Lt (0.173) and L0maks (Y) (0,157) <Lt (0173), the samples come from populations berdristribusi normal , Then from the calculation of product moment correlation between muscle power arm shoulder with the results of shot put, with rhitung> rtable, (0.679)> (0.413), muscle tone back with the results of shot put with rhitung> rtable, (0,532)> (0.413), power relations arm muscles shoulder and back muscle flexibility with shot put results on male students of class XI SMK Taruna Mandiri Pekanbaru, with 0.701 rhitung> Rtable0.413, meaning that there is a relationship together between the shoulder arm muscle power and flexibility of the back muscles with the ability of the results shot put. Keywords: Power Relations shoulder and arm muscles muscle tone back to the shot put results.